CDKL5 Mutations in Boys With Encephalopathy and Early-Onset Intractable Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
Clinical and EEG data of 3 Italian boys (ages 3, 9, and 13 years) with severe early-onset encephalopathy, mental retardation, facial dysmorphisms, and intractable epilepsy were found to carry missense mutations in the CDKL5 gene, in a report from Troina, Italy.